2001
DOI: 10.1107/s0907444901001652
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a small-molecule binding site at the dimer interface of the HIV integrase catalytic domain

Abstract: Integration of the reverse‐transcribed HIV cDNA into the host DNA is a required step in viral replication. The virus‐encoded integrase protein catalyzes the initial DNA breaking and joining reactions that mediate cDNA integration. Here, the identification by X‐ray crystallography of a small‐molecule binding site on the integrase catalytic domain is reported. The small‐molecule family studied consists of a core of arsenic or phosphorus surrounded by four aromatic groups. Two arsenic derivatives were visualized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 32 publications
2
80
0
Order By: Relevance
“…Comparison of Acetylated-Inhibitor with 3,4-dihydroxyphenyltriphenylarsonium bromide, an HIV-1 IN inhibitor that has been shown to also bind at the IN dimer interface, is interesting (32). Our data indicate that Acetylated-Inhibitor binds deep into the dimer interface pocket owing to its ''slim'' structure (see Figs.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Comparison of Acetylated-Inhibitor with 3,4-dihydroxyphenyltriphenylarsonium bromide, an HIV-1 IN inhibitor that has been shown to also bind at the IN dimer interface, is interesting (32). Our data indicate that Acetylated-Inhibitor binds deep into the dimer interface pocket owing to its ''slim'' structure (see Figs.…”
Section: Discussionmentioning
confidence: 87%
“…However, this structure did not include the cognate DNA substrate, which is believed to contribute to the inhibition through formation of a ternary inhibitor:protein:DNA complex. In separate work, a small molecule (3,4-dihydroxyphenyltriphenylarsonium bromide) inhibitor was shown to bind at the HIV-1 IN dimer interface (32). These structural analyses were performed by using the core domain of IN rather than the full-length protein (31,32).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, prior to the recognition of this region as the p75 binding site, there was evidence it could contain hotspots for small molecule binding. Molteni et al [168] reported the structures of two related small molecules (tetraphenylarsonium and dihydroxyphenyltriphenylarsonium) bound to the IN CCD, where they were found to occupy what is now recognized as the IBD-binding cleft (compare panel b of Fig. 5 with Figure 3b of Molteni et al, which shows a similarly rotated view of the CCD).…”
Section: Targeting the P75-ibd Interactionmentioning
confidence: 94%
“…Building on the work of Dyda et al, 12 we performed X-ray crystallographic experiments that demonstrated that this series of compounds bound to a hydrophobic pocket at the dimer interface of the CCD of IN (vide infra). This pocket was first identified as the binding site of tetraarylarsonium ions by X-ray crystallography 13 and later as a part of the recognition domain on IN for the lens epithelial derived growth factor (LEDGF/ p75), 14 a host cell protein involved in protection and trafficking of PICs to transcriptionally active regions of chromatin. 15 Since our series of inhibitors bound to a site remote from the active site and inhibited the 3′-processing activity of the enzyme, we have termed these molecules noncatalytic site integrase inhibitors (NCINIs).…”
mentioning
confidence: 99%